2013
DOI: 10.1175/jas-d-12-0301.1
|View full text |Cite
|
Sign up to set email alerts
|

Typhoon-Position-Oriented Sensitivity Analysis. Part I: Theory and Verification

Abstract: A new sensitivity analysis method is proposed for the ensemble prediction system in which a tropical cyclone (TC) position is taken as a metric. Sensitivity is defined as a slope of linear regression (or its approximation) between state variable and a scalar representing the TC position based on ensemble simulation. The experiment results illustrate important regions for ensemble TC track forecast. The typhoon-positionoriented sensitivity analysis (TyPOS) is applied to Typhoon Shanshan (2006) for the verificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Observing system experiments (OSEs) have shown that dropsonde observations in sensitive regions, depicted by a singular vector method 11 , have strong impact on TC location forecasts in comparison with observations made outside such regions 7 , 8 . However, when a TC reaches the mid-latitudes, its motion becomes sensitive to the present upper-troposphere circulations 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Observing system experiments (OSEs) have shown that dropsonde observations in sensitive regions, depicted by a singular vector method 11 , have strong impact on TC location forecasts in comparison with observations made outside such regions 7 , 8 . However, when a TC reaches the mid-latitudes, its motion becomes sensitive to the present upper-troposphere circulations 12 .…”
Section: Introductionmentioning
confidence: 99%
“…One method of evaluating the origin of TC position errors is through sensitivity analysis, which provides information about how small changes to the initial conditions can impact a forecast metric, such as TC position, at a particular time. Although position forecast sensitivity can exhibit large case-to-case variability and within methods (e.g., Majumdar et al 2006;Wu et al 2009;Hoover et al 2013), previous studies have suggested that TC position forecasts can be sensitive to specific flow features, such as weaknesses in the subtropical ridge, the motion and evolution of midlatitude troughs, the position and speed of the subtropical jet, as well as uncertainty in the 0-h TC steering flow (e.g., Majumdar et al 2006;Peng and Reynolds 2006;Wu et al 2007;Chen et al 2009;Wu et al 2009;Komaromi et al 2011;Gombos et al 2012;Ido and Wu 2013;Nystrom et al 2018). Furthermore, latent heat release associated with a TC and nearby convection can have an important impact on TC motion by modifying the nearby environment (e.g., Wu and Emanuel 1995a,b;Henderson et al 1999;Anwender et al 2008;Harr et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to several adjoint-based methods, such as the singular vector method (SVs; Palmer et al 1998;Buizza and Montani 1999) and the conditional nonlinear optimal perturbation method (Mu, Zhou, and Wang 2009;Wang, Mu, and Huang 2011;Yu et al 2017), ensemble-based methods, such as the ensemble transformation method (ET; Toth 1999, hereafter BT1999) and the ensemble transform Kalman filter method (ETKF; Bishop, Etherton, and Majumdar 2001) are also widely applied in field campaigns (Chang, Zheng, and Raeder 2013;Xie et al 2013). Compared to the adjoint-based methods, the ensemble-based methods do not require adjoint models and are also less computationally demanding (Ancell and Hakim 2007;Ito and Wu 2013).…”
Section: Introductionmentioning
confidence: 99%